The animal question : why nonhuman animals deserve human rights - Cavalieri, Paola, 1950- (Oxford University Press, 2001)
How much do animals matter--morally? Can we keep considering them as second class beings, to be used merely for our benefit? Or, should we offer them some form of moral egalitarianism? Inserting itself into the passionate debate over animal rights, this fascinating, provocative work by renowned scholar Paola Cavalieri advances a radical proposal: that we extend basic human rights to the nonhuman animals we currently treat as "things." Cavalieri first goes back in time, tracing the roots of the debate from the 1970s, then explores not only the ethical but also the scientific viewpoints, examining the debate's precedents in mainstream Western philosophy. She considers the main proposals of reform that recently have been advanced within the framework of today's prevailing ethical perspectives. Are these proposals satisfying? Cavalieri says no, claiming that it is necessary to go beyond the traditional opposition between utilitarianism and Kantianism and focus on the question of fundamental moral protection. In the case of human beings, such protection is granted within the widely shared moral doctrine of universal human rights' theory. Cavalieri argues that if we examine closely this theory, we will discover that its very logic extends to nonhuman animals as beings who are owed basic moral and legal rights and that, as a result, human rights are not human after all.